First-line talazoparib plus enzalutamide versus placebo plus enzalutamide for metastatic castration-resistant prostate cancer: patient-reported outcomes from the randomised, double-blind, placebo-controlled, phase 3 TALAPRO-2 trial - Matsubara, Nobuaki; Azad, Arun A; Agarwal, Neeraj; Saad, Fred; De Giorgi, Ugo; Joung, Jae Young; Fong, Peter C C; Jones, Robert J; Zschäbitz, Stefanie; Oldenburg, Jan; Shore, Neal D; Dunshee, Curtis; et al. (The lancet. Oncology, 2025)
Background - Patients with metastatic castration-resistant prostate cancer have poor prognoses, underscoring the need for novel therapeutic strategies. First-line talazoparib plus enzalutamide significantly improved radiographic progression-free survival compared with placebo plus enzalutamide in men with metastatic castration-resistant prostate cancer in the phase 3 TALAPRO-2 study. We aimed to evaluate patient-reported outcomes in the all-comers cohort of TALAPRO-2, which included patients with and without alterations in homologous recombination repair (HRR) genes. - Methods - TALAPRO-2 is a randomised, double-blind, placebo-controlled, phase 3 trial conducted at 223 hospitals, cancer centres, and medical centres in 26 countries worldwide. Eligible participants were male patients aged 18 years or older (≥20 years in Japan) who were receiving ongoing androgen deprivation therapy, had asymptomatic or mildly symptomatic metastatic castration-resistant prostate cancer, Eastern Cooperative Oncology Group performance status of 0 or 1, and had not received previous life-prolonging systemic therapy for castration-resistant prostate cancer or metastatic castration-resistant prostate cancer. Patients were randomly assigned (1:1) using a centralised interactive web response system and a permuted block size of 4 to oral talazoparib 0·5 mg once daily or placebo, plus oral enzalutamide 160 mg once daily. The funder, patients, and investigators were masked to allocation of talazoparib or placebo; enzalutamide was open-label. Stratification factors were HRR gene alteration status (deficient vs non-deficient or unknown) and previous treatment with docetaxel or abiraterone, or both (yes vs no) in the castration-sensitive setting. The primary endpoint was radiographic progression-free survival by blinded independent central review and has been reported previously. Patient-reported outcomes were assessed as secondary endpoints in the patient-reported outcomes population, which comprised patients from the intention-to-treat population with a baseline patient-reported outcome assessment followed by at least one post-baseline patient-reported outcome assessment. Patient-reported outcomes included mean change from baseline in patient-reported pain symptoms (per Brief Pain Inventory-Short Form [BPI-SF]); global health status/quality of life (GHS/QoL), overall cancer and prostate cancer-specific functioning and symptoms (per European Organisation for Research and Treatment of Cancer [EORTC] Core Quality of Life Questionnaire [QLQ-C30] and Quality of Life Questionnaire-Prostate [QLQ-PR25]); and general health status (per EQ-5D-5L). Time to deterioration in patient-reported pain symptoms (per BPI-SF), and time to definitive deterioration in patient-reported GHS/QoL (per EORTC QLQ-C30) and prostate cancer-specific urinary symptoms (per EORTC-QLQ-PR25) were the other secondary endpoints. This study is registered with ClinicalTrials.gov, NCT03395197, and is ongoing. - Findings - Between Jan 7, 2019, and Sept 17, 2020, 805 patients were enrolled and randomly assigned to treatment irrespective of HRR gene alteration status. 395 patients assigned to talazoparib plus enzalutamide and 398 assigned to placebo plus enzalutamide were included in the patient-reported outcome population. Median follow-up was 28·0 months (IQR 23·9-31·7) for talazoparib plus enzalutamide and 26·8 months (23·4-30·6) for placebo plus enzalutamide. Time to definitive deterioration in GHS/QoL was longer with talazoparib plus enzalutamide versus placebo plus enzalutamide (median 30·8 months [95% CI 27·0-non-estimable] vs 25·0 months [22·9-30·7]; hazard ratio [HR] 0·78 [95% CI 0·62-0·99]; two-sided p=0·038). Median time to definitive deterioration in urinary symptoms was non-estimable (95% CI non-estimable-non-estimable) in the talazoparib plus enzalutamide group and was 35·9 months (95% CI 32·3-non-estimable) in the placebo plus enzalutamide group (HR 0·76 [95% CI 0·54-1·06]; two-sided p=0·11). No clinically meaningful differences (≥10 points) in mean changes from baseline were observed in GHS/QoL, symptom, and functional scales between the treatment groups. No differences were observed between the groups in time to deterioration of pain as measured by the BPI-SF (HR 0·98 [95% CI 0·69-1·40]; two-sided p=0·93), mean pain scores (estimated mean difference in value of worst pain in the past 24 h between treatment groups was −0·1 [95% CI −0·3 to 0·1]; two-sided p=0·27), or general health status as measured by the EQ-5D-5L (estimated mean difference 0·0 [95% CI 0·0-0·0]; two-sided p=0·37). - Interpretation - Talazoparib plus enzalutamide prolonged time to definitive deterioration in GHS/QoL versus placebo plus enzalutamide. Together with clinical efficacy and safety data, these results inform the risk-benefit assessment of talazoparib plus enzalutamide in patients with metastatic castration-resistant prostate cancer in TALAPRO-2. - Funding - Pfizer.